Remote mood monitoring for adults with bipolar disorder: An explorative study of compliance and impact on mental health service use and costs - Simon, J; Budge, K; Price, J; Goodwin, G; Geddes, J (Elsevier, 2017)
Background: Remote monitoring of mood disorders may be an effective and low resource option for patient follow-up, but relevant evidence remains very limited. This study explores real-life compliance and health services impacts of mood monitoring among patients with bipolar disorder in the UK.